2020
DOI: 10.1590/1678-4324-2020180659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma spp. on Growth Promotion and Antioxidative Activity of Pepper Seedlings

Abstract: One of the main challenges in pepper production is to enhance seed germination energy and germination, and to grow healthy nursery plants with strong root system. Trichoderma species colonize roots as they grow and provide season-long benefits to plants, which is why Trichoderma species are widely used as plant growth promoter agents and promoters of plant defence mechanisms. This study evaluated the effectiveness of seed biopriming with Trichoderma isolates for growth promotion of pepper plants in early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Interesting findings were reported by Tančić-Živanovet al, who studied the effects of Trichoderma spp. on the antioxidant activity and growth promotion of pepper seedlings [ 23 ]. Positive correlations were found between activity levels of SOD, CAT, and other enzymes and germination in plants treated with the studied isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Interesting findings were reported by Tančić-Živanovet al, who studied the effects of Trichoderma spp. on the antioxidant activity and growth promotion of pepper seedlings [ 23 ]. Positive correlations were found between activity levels of SOD, CAT, and other enzymes and germination in plants treated with the studied isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results showed that the shoots and roots of the rye seedlings did not always correlate with seedling dry weight. Tančić-Živanov et al [52] observed similar results with the effect of some Trichoderma isolates on early pepper seedlings.…”
Section: Discussionmentioning
confidence: 56%
“…Similar results have been reported in diverse crop seedlings treated with Trichoderma spp. (Alfano et al, 2006;Mastauri et al, 2010;Nayaka et al, 2008;Swain et al, 2021;Tančić-Živanov et al, 2020) In this study, seedlings produced from treated seeds exhibited superior seedling vigor in both physiological and water stress conditions compared to untreated seedlings. Swain et al (2018) reported an elevated vigor index of rice treated with Trichoderma.…”
Section: Effects On Dry Roots and Shoots Weights Of Seedlingsmentioning
confidence: 47%